Antiproliferative and c-myc mRNA suppressive effect of tranilast on newborn human vascular smooth muscle cells in culture. - Miyazawa, K. (1996)
1. Newborn human vascular smooth muscle cells (VSMCs) proliferated faster and were more sensitive to platelet-derived growth factor-BB (PDGF-BB) than those from adults. In this study, we investigated mechanism of the inhibitory effect of tranilast on PDGF-BB-induced proliferation of VSMCs from newborns. 2. Tranilast (30-300 microM) concentration-dependently inhibited the VSMC proliferation in randomly growing cultures stimulated with PDGF-BB. 3. Tranilast (30-300 microM) concentration-dependently inhibited the [3H]-thymidine incorporation into DNA in VSMCs that had been synchronized by 48 h serum depletion and then stimulated by addition of PDGF-BB. However, tranilast had little influence on unscheduled DNA synthesis in quiescent cells or on RNA and protein synthesis, unlike aphidicolin, actimomycin D, and cycloheximide. 4. In synchronized VSMC cultures, tranilast still inhibited the PDGF-BB-induced DNA synthesis even when added 18 h after stimulation of the quiescent cells. The mode of the antiproliferative action of tranilast was different from that of NiCl2, genistein, or staurosporin. In addition, flow cytometry of synchronized VSMCs treated with tranilast revealed a blockade of PDGF-inducible cell-cycle progression at the G1/S checkpoint. 5. Northern blotting showed that tranilast (30-300 microM) concentration-dependently suppressed constitutive c-myc mRNA expression even when added 18 h after PDGF-BB-stimulation of quiescent VSMCs. Tranilast still had an inhibitory effect on the induction of c-myc mRNA when de novo protein synthesis was inhibited by cycloheximide and did not shorten the degradation of c-myc mRNA at the post-transcriptional level, demonstrating that tranilast directly inhibited c-myc mRNA expression at the transcriptional level. 6. These results suggest that the inhibitory effect of tranilast on PDGF-BB-induced proliferation is due to S-phase blockade and may be, at least in part, involved in the direct suppression of c-myc gene expression. Tranilast did not cause cell toxicity and may therefore hold promising potential for the prevention of vascular proliferative diseases.